2020
DOI: 10.1007/s10863-020-09838-4
|View full text |Cite
|
Sign up to set email alerts
|

Functional changes induced by caloric restriction in cardiac and skeletal muscle mitochondria

Abstract: Caloric restriction (CR) is widely known to increase life span and resistance against different types of injuries in several organisms. We have previously shown that mitochondria from livers or brains of CR animals exhibit higher calcium uptake rates and lower sensitivity to calcium-induced mitochondrial permeability transition (mPT), an event related to the resilient phenotype exhibited by these organs. Given the importance of calcium in metabolic control and cell homeostasis, we aimed here to uncover possibl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 43 publications
(47 reference statements)
0
16
0
Order By: Relevance
“…In the heart (but not in skeletal muscle), lower maximal respiratory rates and a reduced rate of hydrogen peroxide release were reported. In this model, no changes in the respiratory control ratios were found (Serna et al, 2020 ).…”
Section: Mitochondrial Metabolismmentioning
confidence: 81%
“…In the heart (but not in skeletal muscle), lower maximal respiratory rates and a reduced rate of hydrogen peroxide release were reported. In this model, no changes in the respiratory control ratios were found (Serna et al, 2020 ).…”
Section: Mitochondrial Metabolismmentioning
confidence: 81%
“…To avoid malnutrition, CR rats were fed with an AIM93G diet supplemented with vitamins and minerals to the same levels as AL animals consumed (34). Details regarding the CR protocol and its effects can be consulted in our previous publications (2931). Prior to the experiments, animals were fasted for 10-12 h, beginning at 19:00.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of CR on mitochondrial Ca 2+ transport are, however, organ-specific (31), and have not been explored in kidneys to date. Kidneys are known to be protected from damage induced by ischemia/reperfusion in animals submitted to dietary restriction or fasting (32,33).…”
Section: Introductionmentioning
confidence: 99%
“…These may be a result of less ROS production or increased antioxidant levels. Indeed, evidence shows that calorie restriction decreases mitochondrial ROS released [19][20][21]. Even though that idea is somehow controversial [22] animal studies have shown that calorie restriction lowers the levels of oxidatively modified lipids [23,24], proteins [25], and DNA [26].…”
Section: Introductionmentioning
confidence: 99%
“…Even though that idea is somehow controversial [22] animal studies have shown that calorie restriction lowers the levels of oxidatively modified lipids [23,24], proteins [25], and DNA [26]. Strikingly, calorie restriction seems to protect cardiac mitochondrial components from ROSinduced oxidative damage [20], in parallel with lower mitochondrial ROS production by this organ [19,21].…”
Section: Introductionmentioning
confidence: 99%